Mesopore Controls the Responses of Blood Clot‐Immune Complex via Modulating Fibrin Network. Issue 3 (24th November 2021) - Wu, Shiyu; Shan, Zhengjie; Xie, Lv; Su, Mengxi; Zeng, Peisheng; Huang, Peina; Zeng, Lingchan; Sheng, Xinyue; Li, Zhipeng; Zeng, Gucheng; Chen, Zhuofan; Chen, Zetao
Abstract: Formation of blood clots, particularly the fibrin network and fibrin network‐mediated early inflammatory responses, plays a critical role in determining the eventual tissue repair or regeneration following an injury. Owing to the potential role of fibrin network in mediating clot‐immune responses, it is of great importance to determine whether clot‐immune responses can be regulated via modulating the parameters of fibrin network. Since the diameter of D‐terminal of a fibrinogen molecule is 9 nm, four different pore sizes (2, 8, 14, and 20 nm) are rationally selected to design mesoporous silica to control the fibrinogen adsorption and modulate the subsequent fibrin formation process. The fiber becomes thinner and the contact area with macrophages decreases when the pore diameters of mesoporous silica are greater than 9 nm. Importantly, these thinner fibers grown in pores with diameters larger than 9 nm inhibit the M1‐polorazation of macrophages and reduce the productions of pro‐inflammatory cytokines and chemokines by macrophages. These thinner fibers reduce inflammation of macrophages through a potential signaling pathway of cell adhesion‐cytoskeleton assembly‐inflammatory responses. Thus, the successful regulation of the clot‐immune responses via tuning of the mesoporous pore sizes indicates the feasibility of developing advanced clot‐immune regulatory materials. Abstract : Tuning mesoporous silica pore size is found to affect blood clot coagulation and change fibrin network structure through regulating fibrinogen adsorption. The regulated fibrin network further modulates the immune response of macrophage via a potential pathway of cell adhesion‐cytoskeleton assembly‐inflammatory response, indicating a feasible strategy to develop advanced clot‐immune regulatory materials.